Plan de comunicación interna para el retorno a oficinas de colaboradores post Covid-19 del Banco Corporativo Americano - Moreno Huamanchumo, Ana Lucía (2020)
The American Corporate Bank is one of the most important banks in Peru and is a regional benchmark in innovation, with 405 agencies and more than 1,800 ATMs throughout the country. On March 11, 2020, the World Health Organization recognizes COVID-19 as a global pandemic and Peru declares a state of national emergency to prevent the spread of the virus in Peruvian territory, including mandatory social isolation and closure. of borders, paralyzing economic, social and labor activities. Given this, the BCA implements remote work for its administrative collaborators and attends its clients with restricted hours in the agencies. This work proposes the internal communication plan for the return to the offices of the collaborators of the Corporate Bank of America, once the quarantine in Peru has been lifted.